Logistic as a Factor to Improve the Integrated Transport and Environmentally Acceptable - Vyshka, Eli; Hajderi, Asllan (Richtmann Publishing, 2012)
The work presented takes in consideration the impact of policies (master) to the state in management of existing infrastructureand the combination of types of transport with the aim of making the environmentally friendly transportation with the climate andresources. The purpose of this document is to provide a summary of transport modeling methodology and results provided to traffic. Thetool used for this project was the city of Tirana, calibrated according to the base year 2007. The model was developed for conductingregional transportation analysis. Material argues that spatial distribution of social networking in combination with the establishment ofhousing choices will be a major factor in increasing the distinct travel miles. The conceptual framework for the day-to-day dynamics isbased on the rhythmic patterns for the need of accumulation and their satisfaction through activities and long-terms projects. Model,through cargo transport (number of vehicles is expected to grow about 9 times) of data on population (which is expected to grow by57%), economic development and travel behavior predicts the development of traffic conditions in the future (which yields 37%higher). These projections are a tool to be used by planners to identify types of transport investments that will be more effective inreducing congestion, improving travel times, as well as meeting the objectives of the Metropolitan Transportation Plan (MTP).